Antecedents of entrepreneurial intentions among students in vocational training programmes. Issue 7 (23rd August 2018) - Galvão, Anderson; Marques, Carla Susana; Marques, Carlos Peixeira
Abstract : Purpose: The purpose of this paper is to contribute to research on individual entrepreneurial intention (IEI) by assessing the importance of entrepreneurship education to students in vocational training programmes and using the theory of planned behaviour (TPB) to analyse these students' entrepreneurial intentions. The family background of the students and their exposure to entrepreneurship subject matter were included as antecedents of TPB components and IEI. Design/methodology/approach: To test the research model, the primary data were collected with questionnaires distributed to students in their last year of vocational training programmes with and without entrepreneurship coursework, in a region of Northern Portugal. The data were analysed using structural equation modelling. Findings: The results show that TPB dimensions substantially contribute to explaining students' IEI. However, their family background makes only a minor contribution, and exposure to entrepreneurship education has no influence on IEI. Research limitations/implications: Given these results, the authors propose a broader discussion is needed of the importance of introducing business classes into the curricula of vocational training programmes. Originality/value: This research's results show that IEI models need to assign greater importance to variables related to previous exposure to entrepreneurial experiences through direct family members. The findings contribute to a fuller understanding of IEI and the factors that precede the formation of this intention among students in training programmes.